Interobserver Agreement in Diagnosing Early-Stage Kienböck Disease on Radiographs and Magnetic Resonance Imaging. (November 2017) - van Leeuwen, Wouter F.; Janssen, Stein J.; Guitton, Thierry G.; Chen, Neal; Ring, David
Background: The appearance of early Kienböck disease on radiographs and magnetic resonance imaging (MRI) may be difficult to distinguish from other conditions that affect the lunate. We aimed to assess the interobserver agreement in the diagnosis of early Kienböck disease when evaluated on different imaging modalities.Methods: Forty-three hand surgeon members of the Science of Variation Group were randomized to evaluate radiographs and 35 hand surgeons to evaluate radiographs and MRI scans of 26 patients for the presence of Kienböck disease, the lunate type, and the ulnar variance. We used Fleiss' kappa analysis to assess the interobserver agreement for categorical variables and compared the κ values between the 2 groups.Results: We found that agreement on the diagnosis of early Kienböck disease was fair (κ, 0.36) among observers who evaluated radiographs alone and moderate (κ, 0.58) among observers who evaluated MRI scans in addition to radiographs, and that the difference in κ values was not statistically significant ( P = .057). Agreement did not differ between observers based on imaging modality with regard to the assessment of the lunate type ( P = .75) and ulnar variance ( P = .15).Conclusions: We found, with the numbers evaluated, a notable but nonsignificant difference in agreement in favor of observers who evaluated MRI scans in addition to radiographs compared with radiographs alone. Surgeons should be aware that the diagnosis of Kienböck disease in the precollapse stages is not well defined, as evidenced by the substantial interobserver variability.